Family members' knowledge and support for medication adherence in patients with schizophrenia - Fadilah, Lailatul; Dewi, Sri Handayani; Sari, Cucuk Kunang (JOURNAL OF Mental Health Concerns, 2025)
Background: Schizophrenia is a serious mental disorder characterized by disorganization of the sufferer's thoughts, feelings and thoughts. The factors, namely family knowledge regarding mental health (schizophrenia) in adherence to taking routine medication and family support, are factors that greatly influence adherence to medication in the recovery of schizophrenia patients. Purpose: To identify family members' knowledge and support for medication adherence in patients with schizophrenia. Method: A quantitative research. The research design used Cross Sectional with a purposive sampling method, and a sample of 80 people. This research instrument used the schizophrenia knowledge instrument, the family support instrument for medication adherence and the MMS A-8 instrument. Results: Based on the results of the Chi-Square test, the results showed a relationship between knowledge and medication adherence (p value 0.794) as well as a relationship between family support (p value 0.341) with medication adherence. Conclusion: There is no relationship between knowledge and adherence to taking medication and there is no relationship between family support in schizophrenia patients in the working area of the Cadasari Health Center, Pandeglang Regency. Keywords: Family Support; Knowledge; Medication Compliance; Schizophrenia.